Salvage Reirradiation Options for Locally Recurrent Prostate Cancer: A Systematic Review - Zhong, Jim; Slevin, Finbar; Scarsbrook, Andrew F.; Serra, Maria; Choudhury, Ananya; Hoskin, Peter J.; Brown, Sarah; Henry, Ann M. (Frontiers in Oncology, 2021)
Background: Reirradiation using brachytherapy (BT) and external beam radiation therapy (EBRT) are salvage strategies with locally radiorecurrent prostate cancer. This systematic review describes the oncologic and toxicity outcomes for salvage BT and EBRT (including Stereotactic Body Radiation Therapy (SBRT)). Methods: An International Prospective Register of Systematic Reviews (PROSPERO) registered (#211875) study was conducted using Preferred Reporting Items for Systematic reviews and Meta-analyses (PRISMA) guidelines. EMBASE and MEDLINE databases were searched from inception to December 2020. For BT, both low dose rate (LDR) and high dose rate (HDR) BT techniques were included. Two authors independently assessed study quality using the 18-item Modified Delphi technique. Results: A total of 39 eligible studies comprising 1967 patients were included (28 BT and 11 SBRT). In 35 studies (90%), the design was single centre and/or retrospective and no randomised prospective studies were found. Twelve BT studies used LDR only, 11 HDR only, 4 LDR or HDR and 1 pulsed-dose rate only. All EBRT studies used SBRT exclusively, four with Cyberknife alone and 7 using both Cyberknife and conventional linear accelerator treatments. Median (range) modified Delphi quality score was 15 (6-18). Median (range) follow-up was 47.5 months (13-108) (BT) and 25.4 months (21-44) (SBRT). For the LDR-BT studies, the median (range) 2-year and 5-year bRFS rates were 71% (48-89.5) and 52.5% (20-79). For the HDR-BT studies, the median (range) 2-year and 5-year bRFS rates were 74% (63-89) and 51% (45-65). For the SBRT studies, the median (range) 2-year bRFS for the SBRT group was 54.9% (40-80). Mean (range) acute and late grade≥3 GU toxicity rates for LDR-BT/ HDR-BT/ SBRT were 7.4%(0-14)/ 2%(0-14)/ 2.7%(0-8.7) and 13.6%(0-30)/ 7.9%(0-21.3%)/ 2.7%(0-8%). Mean (range) acute and late grade≥3 GI toxicity rates for LDR-BT/ HDR-BT/ SBRT were 6.5%(0-19)/ 0%/ 0.5%(0-4%) and 6.4%(0-20)/ 0.1%(0-0.9)/ 0.2%(0-1.5). One third of studies included Patient Reported Outcome Measures (PROMs). Conclusions: Salvage reirradiation of radiorecurrent prostate cancer using HDR-BT or SBRT provides similar biochemical control and acceptable late toxicity. Salvage LDR-BT is associated with higher late GU/GI toxicity. Challenges exist in comparing BT and SBRT from inconsistencies in reporting with missing data, and prospective randomised trials are needed.